2016
DOI: 10.18632/oncotarget.11486
|View full text |Cite
|
Sign up to set email alerts
|

Candidate germline polymorphisms of genes belonging to the pathways of four drugs used in osteosarcoma standard chemotherapy associated with risk, survival and toxicity in non-metastatic high-grade osteosarcoma

Abstract: This study aimed to identify associations between germline polymorphisms and risk of high-grade osteosarcoma (HGOS) development, event-free survival (EFS) and toxicity in HGOS patients treated with neo-adjuvant chemotherapy and surgery.Germline polymorphisms of 31 genes known to be relevant for transport or metabolism of all four drugs used in HGOS chemotherapy (methotrexate, doxorubicin, cisplatin and ifosfamide) were genotyped in 196 patients with HGOS and in 470 healthy age and gender-matched controls. Of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 34 publications
1
62
0
Order By: Relevance
“…The study characteristics of the 28 articles included, all were candidate gene studies published between 2008 and 2017, are shown in Table 1 . Most were cohort studies (Wang et al, 2008 ; Filipski et al, 2009 ; Goekkurt et al, 2009 ; Chen et al, 2010 ; Khrunin et al, 2010a , 2012 , 2014 ; KimCurran et al, 2011 ; Tzvetkov et al, 2011 ; Erculj et al, 2012 ; Iwata et al, 2012 ; Windsor et al, 2012 ; Xu et al, 2012 , 2013 ; Zhang and Zhou, 2012 ; Zhang et al, 2012 ; Hinai et al, 2013 ; Khokhrin et al, 2013 ; Lamba et al, 2014 ; Yuan et al, 2015 ; Hattinger et al, 2016 ; Powrozek et al, 2016 ; Chang et al, 2017 ) and none were genome wide association studies (GWAS). Key details of subject characteristics [e.g., ethnicity and inclusion criteria (Sprowl et al, 2012 )], type of chemotherapy regimens (Erculj et al, 2012 ; Sprowl et al, 2012 ; Powrozek et al, 2016 ), and nephrotoxicity criteria (Goekkurt et al, 2009 ; Kim et al, 2012 ; Khrunin et al, 2014 ) were not reported in some studies.…”
Section: Resultsmentioning
confidence: 99%
“…The study characteristics of the 28 articles included, all were candidate gene studies published between 2008 and 2017, are shown in Table 1 . Most were cohort studies (Wang et al, 2008 ; Filipski et al, 2009 ; Goekkurt et al, 2009 ; Chen et al, 2010 ; Khrunin et al, 2010a , 2012 , 2014 ; KimCurran et al, 2011 ; Tzvetkov et al, 2011 ; Erculj et al, 2012 ; Iwata et al, 2012 ; Windsor et al, 2012 ; Xu et al, 2012 , 2013 ; Zhang and Zhou, 2012 ; Zhang et al, 2012 ; Hinai et al, 2013 ; Khokhrin et al, 2013 ; Lamba et al, 2014 ; Yuan et al, 2015 ; Hattinger et al, 2016 ; Powrozek et al, 2016 ; Chang et al, 2017 ) and none were genome wide association studies (GWAS). Key details of subject characteristics [e.g., ethnicity and inclusion criteria (Sprowl et al, 2012 )], type of chemotherapy regimens (Erculj et al, 2012 ; Sprowl et al, 2012 ; Powrozek et al, 2016 ), and nephrotoxicity criteria (Goekkurt et al, 2009 ; Kim et al, 2012 ; Khrunin et al, 2014 ) were not reported in some studies.…”
Section: Resultsmentioning
confidence: 99%
“…We found 14 studies regarding ERCC polymorphisms, including one meta-analysis and one commentary, both of which were excluded. One study [ 19 ] was excluded due to lack of detailed data. Eleven studies met our criteria and were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…However, the prognosis for OS patients remains poor even with the help of chemotherapy because some OS are resistant to chemotherapy and radiation therapy [4-6]. Thus, great efforts have been made to elucidate the mechanisms underlying the invasion and chemo-resistance of OS [7-10]. In specific conditions, the bad sensitivity towards a certain chemotherapy may be resulted from the enhanced anti-apoptotic potentials of the cancer cells [11-13].…”
Section: Introductionmentioning
confidence: 99%